2022
DOI: 10.3390/biomedicines10081871
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Formed by the Promoter Region of the hTERT Gene: Structure-Driven Effects on DNA Mismatch Repair Functions

Abstract: G-quadruplexes (G4s) are a unique class of noncanonical DNAs that play a key role in cellular processes and neoplastic transformation. Herein, we focused on the promoter region of human TERT oncogene, whose product is responsible for the immortality of cancer cells. It has been shown by chemical probing and spectroscopic methods that synthetic 96-nt DNAs modeling the wild-type G-rich strand of the hTERT promoter and its variants with G>A point substitutions corresponding to somatic driver mutations fold int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Strong specific interactions of G4s with MMR proteins MutS and MutL from various organisms including E. coli , N. gonorrhoeae , R. sphaeroides , and humans have been described previously [ 14 , 15 , 31 , 32 ]. However, the biological significance of G4 recognition by cellular proteins is not always clear.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Strong specific interactions of G4s with MMR proteins MutS and MutL from various organisms including E. coli , N. gonorrhoeae , R. sphaeroides , and humans have been described previously [ 14 , 15 , 31 , 32 ]. However, the biological significance of G4 recognition by cellular proteins is not always clear.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, we aimed to answer the question of whether a single G4 inserted into a DNA plasmid can affect the activity of ngMutL with an endonuclease function in the methyl-independent MMR inherent in eukaryotic organisms. It has previously been shown that ngMutL recognizes and preferentially binds isolated DNA G4 with high affinity, but, nevertheless, inefficiently cleaves the phosphodiester bonds inside of the G4-motif in TERT promoter fragment [ 32 ]. To clarify this issue, we analyzed ngMutL-mediated cleavage of the G4-pUC plasmid, which contained an extrahelical stable G4, as well as reference plasmids, G/C-pUC and G/T-pUC.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have tested the ngMutL ability to cleave the single-stranded DNA containing a tandem three-quadruplex structure of the hTERT promoter and revealed that it is significantly suppressed by the stable G4 scaffold [ 29 ]. Herein, we evaluated the efficiency of ngMutL-mediated cleavage of the single parallel G4 formed by the d(GGGT)4 sequence, which is stabilized in a DNA duplex context due to the lack of the site complementary to the G4-forming motif in the opposite strand, (95G4/76M).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the ngMutL endonuclease binds nonspecifically to DNA, showing no preferential affinity for mismatch sites [ 25 , 26 , 27 , 28 ]. Nevertheless, we recently discovered the ability of this enzyme to recognize and effectively bind the single parallel G4 formed by the d(GGGT) 4 sequence, as well as the three-quadruplex structure formed by the promoter region of the human telomerase reverse transcriptase ( hTERT ) gene; at the same time, ngMutL has been shown to not hydrolyze DNA within the tandem G4s [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The G4-stabilizing properties of the isolated bis-NHC Au­(I) complexes, AuB2 , AuB3 , and AuC1–3 , were assessed via the FRET DNA melting assay using a panel of five G4s in a 5:1 stoichiometry [Au­(I) NHC complex: G4, see the Experimental Section for details]. The G4s were chosen to represent both the telomeric (hTelo) and promoter ( cKIT1 , cKIT2 , BCL2 , and hTERT ) regions of the polynucleotide, as well as different G4 strand orientations such as hybrid-mixed (3 + 1) (hTelo and BCL2 ) and parallel ( cKIT1 , cKIT2 , and hTERT ). The bis-caffeine complex AuTMX 2 was tested as a benchmark, also because its cKIT2 and BCL2 G4-stabilizing properties have never been reported so far. , …”
Section: Resultsmentioning
confidence: 99%